2017
DOI: 10.11591/ijpeds.v8.i1.pp279-289
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Control Implementation for Inverter Based Harmony Search Algorithm

Abstract: This research implements a PI controller based on harmony search (HS) optimization algorithm for voltage source inverter to improve the output performance under step load change conditions. The HS algorithm aims to handle the trial and error procedure used in finding the PI parameters and then apply the proposed control algorithm via the eZdsp TMS320F28355 board to link the inverter prototype with the Matlab Simulink. The mean absolute error (MAE) is used as an optimization problem to minimize the output volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…If the inverter is not operating properly, the injected power can cause voltage and frequency oscillations and poor grid power quality. The control algorithms of the inverters are a critical factor to assure that the injected power has low harmonic content and complies with international standards [5,12]. Some of these, such as the IEEE 1547-2003, determine harmonics limits for the current injected into the grid.…”
Section: Introductionmentioning
confidence: 99%
“…If the inverter is not operating properly, the injected power can cause voltage and frequency oscillations and poor grid power quality. The control algorithms of the inverters are a critical factor to assure that the injected power has low harmonic content and complies with international standards [5,12]. Some of these, such as the IEEE 1547-2003, determine harmonics limits for the current injected into the grid.…”
Section: Introductionmentioning
confidence: 99%
“…However it is observed that the controller performance deteriorates under varied drive operating conditions. It has been found from literature studies that the use of the stochastic optimization techniques for obtaining the optimized values of PI controllers are finding increased importance [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%